A rare complication following the removal of a palatal tumour. Issue 1 (January 2017) - Ellabban, Islam; Hamed, Mohamed; Hassan, Khalid
Abstract : Postextubation stridor is a condition that has been fairly reported in the literature of anaesthesiologists, yet scarcely reported in that of maxillofacial surgeons. Postextuabtion stridor has multiple aetiologies and risk factors that can promote this condition. However, there are techniques that can predict the occurrence of this complication. More importantly, the question remains how to have a prophylactic approach towards this condition. We present a case of a 60-year-old female patient who endured this complication after removal of a palatal pleomorphic adenoma.